The regulatory network of epithelial-mesenchymal transition-associated non-coding RNAs in thyroid cancer: molecular mechanisms, clinical implications, and therapeutic strategies - Zhao, Rui; Tian, Jiaju; Peng, Jing; Ma, Ruiting; Fu, Songbo (Frontiers in Oncology, 2025)
Thyroid cancer represents the most prevalent malignant neoplasm within the endocrine system, exhibiting a steadily increasing global incidence. Non-coding RNAs (ncRNAs) have emerged as a pivotal focus in thyroid cancer research, demonstrating significant involvement in tumor progression through epigenetic regulation. Contemporary studies reveal widespread dysregulation of ncRNA expression profiles in thyroid malignancies, where differentially expressed ncRNAs exert either tumor-suppressive or oncogenic functions by modulating epithelial-mesenchymal transition (EMT) mechanisms. This review synthesizes current knowledge on EMT-related ncRNA mechanisms driving thyroid carcinogenesis and evaluates their diagnostic and therapeutic potential. By elucidating these molecular interactions, we aim to catalyze discovery of novel ncRNA-mediated pathways, advance targeted treatment strategies, and ultimately enhance clinical outcomes for thyroid cancer patients.